2012
DOI: 10.1134/s0030400x12050062
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopic and quantum chemical studies on hydantoin

Abstract: In this study the geometry optimization of monomeric and dimeric forms (D1, D2, and D3) of hydantoin molecule were done using DFT method employing 6-31++G(d, p) basis set. Harmonic and anharmonic wavenumbers and infrared intensities were computed at the same theory level. Experimental IR spectrum was recorded in the region 400-4000 cm -1 . It has also been characterized by 1 H and 13 C NMR spectrum. The hydrogen bond (HB) interaction of hydantoin was analyzed via dimers of hydantoin. Detailed vibrational waven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…10 The vibrational spectra of the normal and enriched isotopologues were also recorded at low resolution in the infrared regime. 11,12 The first high-resolution laboratory spectroscopy study of hydantoin in the gas phase was reported in 2017 using millimeter-wave (mmw) spectroscopy in the frequency range 90 to 370 GHz. 13 Molecular constants for the ground state and two low-lying vibrationally excited states were reported, which can be useful for high frequency radio astronomical observations where molecular vibrationally excited states can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…10 The vibrational spectra of the normal and enriched isotopologues were also recorded at low resolution in the infrared regime. 11,12 The first high-resolution laboratory spectroscopy study of hydantoin in the gas phase was reported in 2017 using millimeter-wave (mmw) spectroscopy in the frequency range 90 to 370 GHz. 13 Molecular constants for the ground state and two low-lying vibrationally excited states were reported, which can be useful for high frequency radio astronomical observations where molecular vibrationally excited states can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental frequencies of the two low-lying vibrational modes in the gas phase have not been directly observed yet. Ildiz et al (2012Ildiz et al ( , 2013 presented theoretically predicted infrared spectra of hydantoin by using the DFT(B3LYP) and MP2 levels of approximation, and showed that Ar-matrix isolated infrared spectra observed above 500 cm −1 were fully assigned with the help of the above information. Their calculation also showed that there are two low-lying vibrational modes below 200 cm −1 , both of which are designated to be torsional motions of a five-membered ring.…”
Section: Resultsmentioning
confidence: 99%
“…The number of the observed intense lines in an individual bunch is larger than expected when we attribute them to the spectral lines in the ground vibrational state. As mentioned in the Introduction, data obtained using infrared and Raman spectroscopy (Saito & Machida 1978), and via several theoretical calculations (Ildiz et al 2012(Ildiz et al , 2013Belaidi et al 2015), suggest that there are at least two low-lying vibrational excited states (below 300 K, or 200 cm −1 ) for hydantoin. Initial assignments were made possible by assuming that the observed intense lines are due to the b-type R-branch transition in the ground state and in two excited vibrtaional states.…”
Section: Spectral Analysismentioning
confidence: 99%
See 2 more Smart Citations